Experimental study of mercury removal from exhaust gases - Wdowin, M.; Wiatros-Motyka, Malgorzata M.; Panek, R.; Stevens, Lee A.; Franus, W.; Snape, Colin E. (Elsevier, 2014)
An initial study has been made of the use of synthetic zeolites for mercury capture from exhaust gases. Synthetic zeolites (Na-X and Na-P1), and for comparison a natural zeolite (clinoptilolite) and activated carbon with bromine (AC/Br) were tested for mercury uptake from a gaseous stream. The materials were subjected to mercury adsorption tests and their thermal stability was evaluated. The untreated synthetic zeolites had negligible mercury uptake, but after impregnation with silver, the adsorption of mercury was markedly improved. The synthetic zeolite Na-X impregnated with silver adsorbed significantly more mercury before breakthrough than the activated carbon impregnated with bromine, indicating the potential of zeolite derived from coal fly ash as a new sorbent for capture of mercury from flue gases.